Spectrum Analyzer Based on Dispersive Fiber - L. A. Aronov; S. V. Grachev; V. N. Ushakov (Известия высших учебных заведений России: Радиоэлектроника)
Functioning of spectrum analyzer based on optical chirp-transform is observed. Optical elements with frequency dispersion are used to perform spectrum analysis. Scheme and attainable characteristics are presented.